2019
DOI: 10.21608/edj.2019.73999
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two-stage versus one-stage injection in reducing discomfort during inferior alveolar nerve block in children

Abstract: Background: Inferior alveolar nerve block (IANB) anesthesia is a painful procedure & many attempts are made to render the injection painless, especially in children. Aim: To assess discomfort expressed during modified two-stage IANB injection versus one-stage injection in 8-10 years old children. Subjects & Methods: Sixty children were randomly & equally allocated to either intervention group (two-stage) or control group (one-stage). For all patients, topical anesthesia gel was applied. Intervention group: A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Kappa test showed that there was an almost perfect inter-examiner agreement concerning SEM Scale values for both groups A and B as shown in table (1). Correlations:…”
Section: Inter-examiner Reliabilitymentioning
confidence: 81%
See 2 more Smart Citations
“…Kappa test showed that there was an almost perfect inter-examiner agreement concerning SEM Scale values for both groups A and B as shown in table (1). Correlations:…”
Section: Inter-examiner Reliabilitymentioning
confidence: 81%
“…The median score of WBFPS for group A was three and the median score for group B was zero as shown in figure (1). Mann-Whitney test showed that there was no significant difference in WBFPS values between group A and group B (p = 0.079).…”
Section: Wrong-baker Face Pain Scale (Wbfps)mentioning
confidence: 88%
See 1 more Smart Citation